2021
DOI: 10.3390/brainsci11010064
|View full text |Cite
|
Sign up to set email alerts
|

Cranio-Vertebral Junction Triangular Area: Quantification of Brain Stem Compression by Magnetic Resonance Images

Abstract: (1) Background: Most of the currently used radiological criteria for craniovertebral junction (CVJ) were developed prior to the popularity of magnetic resonance images (MRIs). This study aimed to evaluate the efficacy of a novel triangular area (TA) calculated on MRIs for pathologies at the CVJ. (2) Methods: A total of 702 consecutive patients were enrolled, grouped into three: (a) Those with pathologies at the CVJ (n = 129); (b) those with underlying rheumatoid arthritis (RA) but no CVJ abnormalities (n = 279… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…It was reported that the C1-2 angle was significantly enlarged while the C2-7 angle was reduced significantly after the posterior atlantoaxial fusion surgery for patients of os odontoideum. [7][8][9][10] This evidence supports the prediction that the subaxial alignment parameters will also change in response to the correction of the C1-2 angle. In the present case, we noted the range of motion at the C3-4 level between neck flexion and extension increased from 4 degrees preoperatively to 9 degrees postoperatively.…”
Section: Discussionsupporting
confidence: 82%
“…It was reported that the C1-2 angle was significantly enlarged while the C2-7 angle was reduced significantly after the posterior atlantoaxial fusion surgery for patients of os odontoideum. [7][8][9][10] This evidence supports the prediction that the subaxial alignment parameters will also change in response to the correction of the C1-2 angle. In the present case, we noted the range of motion at the C3-4 level between neck flexion and extension increased from 4 degrees preoperatively to 9 degrees postoperatively.…”
Section: Discussionsupporting
confidence: 82%
“…Our previous study demonstrated that a TA value greater than 1.36 cm 2 was highly associated with myelopathy. 18 The combined conclusions of both studies suggested that anterior odontoidectomy should be highly considered for those patients who had a TA value greater than 2.5 cm 2 . Once the TA value was larger than 2.5 cm 2 , it was less likely to have a TA smaller than 1.36 cm 2 via the posterior approach only, either with decompression or not.…”
Section: Discussionmentioning
confidence: 98%
“…It has been well reported by many researchers that the retro-odontoid mass tissue disappeared after fixation of the CVJ. 14,17,18,25 Chang et al 17 observed that the TA decreased immediately after the surgery and continued to decrease until 2 years after surgery. In this study, the ΔTA was 1.18 cm 2 in patients who had combined anterior and posterior decompression surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations